Maize Bran Particle Size Governs the Community Composition and Metabolic Output of Human Gut Microbiota in in vitro Fermentations - Thakkar, Riya D.; Tuncil, Yunus E.; Hamaker, Bruce R.; Lindemann, Stephen R. (Frontiers in Microbiology, 2020)
Differences in the chemical and physical properties of dietary fibers are increasingly known to exert effects on their fermentation by gut microbiota. Here, we demonstrate that maize bran particle size fractions show metabolic output and microbial community differences similar to those we previously observed for wheat brans. As for wheat brans, maize bran particles varied in starch and protein content and in sugar composition with respect to size. We fermented maize bran particles varying in size in vitro, measuring their metabolic fate (i.e. short-chain fatty acids, SCFAs) and resulting community structure (via 16S rRNA amplicon sequencing). Metabolically, acetate, propionate, butyrate and total SCFA production were size-dependent. 16S rRNA sequencing revealed that the size-dependent SCFA production was linked to divergent microbial community structures, which exerted effects at fine taxonomic resolution (the genus and species level). These results further suggest that the physical properties of bran particles, such as size, are important variables governing microbial community compositional and metabolic responses.